Antioxidant properties of 5 herbal plants based of pharmacophore modeling - Sam Ezekiel, Radhakrishnan; Mohammad Farhan, Ariffeen Rosli; Ardy Mursyid, Romli; Tiara Nales, Nyawai; Racheal, James; Mohd. Razip, Asaruddin (2016)
Malaysian medicinal plants are known to exert therapeutic effects. We have evaluated some species namely Moringa oleifera, Clinacanthus nutans, Rhodomyrtus tomentosa, Arctium lappa and Sonneratia alba for their antioxidant properties assisted by using pharmacophore modeling approach. We displayed five major compounds from each plant namely: 3-caffeoylquinic, benzylglucosinolate, kaempferol, leucodelphinidin and quercetin (Moringa oleifera), adenosine, arctigenin, arctiin, kaempferol, and solasonine (Arctium lappa), 2-cis-entadamine A, phaeophytin, clinamides B, isovetaxin, and vitexin (Clinancathus nutans), 5-hydroxymethylfurfural, alphitolic acid, betulin, mtheyl gallate, oleanolic acid (Sonneratia alba) and lupeol, rhodomyrtosone A, rhodomyrtosone B, rhodomyrtosone C and rhodomyrtosone D (Rhodomyrtus tomentosa).